2021
DOI: 10.35633/inmateh-63-42
|View full text |Cite
|
Sign up to set email alerts
|

Using the Discrete Element Method to Analyze and Calibrate a Model for the Interaction Between a Planting Device and Soil Particles

Abstract: Dynamic soil behaviour at the contact interface during transplanting makes it difficult to ensure transplanting quality. To solve this problem, the Hertz-Mindlin with bonding contact model was used to calibrate the parameters of soils in Inner Mongolia. Based on the response surface design principle, four-factor and three-level tests were performed using the repose angle as an evaluation index, and the following influence factors were considered: the soil-soil restoration coefficient, the soil-steel restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The parameters were adjusted several times, and the optimal results are shown in Table 2. To improve the accuracy of the simulation and ensure the efficiency of the calculation, soil particles were set as spherical particles with a filling radius of 3 mm, and the basic parameters were determined according to the literature [32,33]. As shown in Figure 5, a simulation model of the soil and compactness meters is established, and the dropping speed of the compactness meter is set to 50 mm/s.…”
Section: Establishment Of the Soil Modelmentioning
confidence: 99%
“…The parameters were adjusted several times, and the optimal results are shown in Table 2. To improve the accuracy of the simulation and ensure the efficiency of the calculation, soil particles were set as spherical particles with a filling radius of 3 mm, and the basic parameters were determined according to the literature [32,33]. As shown in Figure 5, a simulation model of the soil and compactness meters is established, and the dropping speed of the compactness meter is set to 50 mm/s.…”
Section: Establishment Of the Soil Modelmentioning
confidence: 99%
“…In order to ensure that the simulated soil can accurately represent the actual soil conditions, the determination of relevant physical parameters and the calibration of simulation parameters have been completed for the sandy loam soil in Inner Mongolia (Zeng et al, 2021), as shown in Table 2. The simplification is carried out separately for the structural characteristics of sandy loam soils.…”
Section: Discrete Element Simulation Analysis Of Transplanting Processmentioning
confidence: 99%